2014
DOI: 10.3727/096368912x658944
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant Effects by Bilateral and Unilateral Transplantation of GABA-Producing Cells into the Subthalamic Nucleus in an Acute Seizure Model

Abstract: Neural transplantation of GABA-producing cells into key structures within seizure-suppressing circuits holds promise for medication-resistant epilepsy patients not eligible for resection of the epileptic focus. The substantia nigra pars reticulata (SNr), a basal ganglia output structure, is well known to modulate different seizure types. A recent microinjection study by our group indicated that the subthalamic nucleus (STN), which critically regulates nigral activity, might be a more promising target for focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…This evidence has guided a straightforward concept that grafting of cells that release the inhibitory neurotransmitter GABA into the seizure focus would greatly restrain SRS (Loscher et al, 2008). Indeed, grafting of GABA-soaked beads, immortalized GABA-ergic cells, cells engineered to produce GABA or fetal GABA-ergic cells into the epileptic foci produces anticonvulsant effects in a variety of animal models (Kokaia et al, 1994; Loscher et al, 1998; Gernert et al, 2002; Thompson, 2005; Castillo et al, 2006, 2008; Nolte et al, 2008; Handreck et al, 2014). However, anti-seizure effects were either modest or transient in most of these studies, presumably because of poor graft cell survival.…”
Section: Efficacy Of Primary Gaba-ergic Cell Grafts For Mediating mentioning
confidence: 99%
“…This evidence has guided a straightforward concept that grafting of cells that release the inhibitory neurotransmitter GABA into the seizure focus would greatly restrain SRS (Loscher et al, 2008). Indeed, grafting of GABA-soaked beads, immortalized GABA-ergic cells, cells engineered to produce GABA or fetal GABA-ergic cells into the epileptic foci produces anticonvulsant effects in a variety of animal models (Kokaia et al, 1994; Loscher et al, 1998; Gernert et al, 2002; Thompson, 2005; Castillo et al, 2006, 2008; Nolte et al, 2008; Handreck et al, 2014). However, anti-seizure effects were either modest or transient in most of these studies, presumably because of poor graft cell survival.…”
Section: Efficacy Of Primary Gaba-ergic Cell Grafts For Mediating mentioning
confidence: 99%
“…Targeting interneurons to a critical, common seizure network node or "choke point," 46 or to a neuromodulatory center that broadly projects to cortical areas, could prove an effective method for treating both focal and generalized forms of epilepsy. 21,36 Finally, the recipient background may influence the cellular development and circuit integration of transplanted interneurons. Epilepsies arise from numerous etiologies, including structural, genetic, infectious, immune, and met-…”
Section: Targeting Human Epilepsies With Interneuron Transplantation:mentioning
confidence: 99%
“…However, considering the preponderance of interneuron pathologies in TLE, more recent studies have focused on transplanting GABAergic interneurons/progenitors into seizure foci. Preclinical studies in animal models of epilepsy have shown the efficacy of GABAergic interneuron/progenitor transplantation in ameliorating seizures ( Löscher et al, 1998 ; Hattiangady et al, 2008 ; Baraban et al, 2009 ; Calcagnotto et al, 2010 ; Handreck et al, 2012 ; Maisano et al, 2012 ; Hunt et al, 2013 ; Cunningham et al, 2014 ; Hammad et al, 2014 ; Henderson et al, 2014 ; Table 1 ). Pioneering work by Löscher et al (1998) revealed that transplanting rat fetal GABAergic neurons into the substania nigra (SN) led to a dramatic increase in afterdischarge thresholds and significant reductions in the severity of seizures.…”
Section: Gabaergic Interneuron/progenitor Transplantation To Treat Epmentioning
confidence: 99%
“…In 2012, Handreck et al observed the anticonvulsant effects of GABA-producing cells implanted bilaterally/unilaterally into the subthalamic nucleus (STN) using a pentylenetetrazole (PTZ)-induced acute seizure model in adult rats. In addition, they observed that grafting into the STN caused more pronounced anticonvulsant effects than grafting into the SN ( Handreck et al, 2012 ). In these two studies, GABA-producing cells were placed into sites that modulate seizures rather than the seizure focus.…”
Section: Gabaergic Interneuron/progenitor Transplantation To Treat Epmentioning
confidence: 99%